Подвал купеческого дома конца первой половины XIV века из Азака - Масловский, А.Н. (Степи Европы в эпоху средневековья, 2008)
The paper presents materials of a rich dwelling dated back to the mid of the 14th century. This complex is the first object which may be connected with the conflict between the Italians and the authorities of the Golden Horde in autumn, 1343. A great bulk of grain and many bags of flour as well as the richness of finds made it possible to presume that the dwelling belonged to a grain dealer. The ceramic finds from the dwelling precisely enough reflect the most essential features of Azak ceramic complex of that period. Among the main directions of its variation are decreasing of a portion of polished and ornamented ceramics made in the Golden Horde centers and replacement of the Byzantine slip ceramics by the production of towns of the Southeastern Crimea. The peculiarities of this particular period are the regularity of finds of Khorezm stamped ceramics, a significant amount of vessels of Majar manufacture, and some series of slip bowls of the East Crimean manufacture distinguished by the style of their decoration.